The redistributive role of government social security transfers on inequality in China - Meng Cai; Ximing Yue (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
The purpose of this work is to evaluate the redistributive role of government social security transfers on inequality in China. We attempt to answer two questions. First, does inequality of after-transfer income narrow, compared to that of before-transfer income? Second, given the scale and distribution of existing government social security transfers, will a small percentage increase in the transfers narrow or widen the inequality of total income? By employing the methodologies of the Musgrave-Thin (MT) index and decomposition of the Gini coefficient of total income by its sources, we find a positive answer to the first question and a negative answer to the second question. Government social security transfers have a positive role on inequality in the sense that the Gini coefficient of after-transfer income is smaller than that of before-transfer income. However, government social security transfers have a negative role on inequality, as current inequality will go up if there is a universal increase in government social security transfers for all recipients. Of all the components of government social security transfers, formal sector pension benefits and medical expense reimbursements are disequalizing, whereas the dibao and rural pension benefits are equalizing.
Keywords: H23; H55; O23; P35; 330; China; inequality; social security; taxes; transfers